Tongue pressure as a novel biomarker of spinal and bulbar muscular atrophy - Mano, Tomoo; Katsuno, Masahisa; Banno, Haruhiko; Suzuki, Keisuke; Suga, Noriaki; Hashizume, Atsushi; Araki, Amane; Watanabe, Hirohisa; Tanaka, Seiya; Yamamoto, Masahiko; Sobue, Gen (Neurology, 2014)
This study aimed to explore the reliability and validity of tongue pressure measurement as a quantitative evaluation of swallowing function in patients with spinal and bulbar muscular atrophy (SBMA). This study enrolled 47 genetically confirmed patients with SBMA and 38 age- and sex-matched healthy controls. In both groups we measured tongue pressure using an intraoral pressure probe and assessed questionnaires that evaluated swallowing functions. We then analyzed the relationship between tongue pressure, functional scales, and the muscle weakness of other regions. Levels of tongue pressure were decreased in patients with SBMA within 3 years from the onset of the disease compared to healthy controls (SBMA 15.3 ± 6.4 kPa; healthy controls 37.3 ± 9.6 kPa; p < 0.001). Test-retest analysis showed a high reliability in patients with SBMA (intraclass correlation coefficient = 0.986). Tongue pressure showed a strong correlation with bulbar-related functional scales. Decrease of tongue pressure was detected in patients who reported no subjective dysphagia, and repetition of swallowing compensated for tongue weakness in such subjects. In patients with SBMA, tongue pressure more strongly correlates with the strength of pharyngeal, neck, and upper limb musculatures than with that of the lower limbs. Tongue pressure measurement is reliable and reflects swallowing function in patients with SBMA. The muscle strength of the tongue appears to decrease in SBMA before the awareness of subjective dysphagia, suggesting that tongue pressure measurement is a novel biomarker of SBMA and is applicable to early-stage detection.